Physico-chemical Evaluation of Some Introduced Date Fruits Cultivars grown under Sudanese conditions - Saeed, Islam K.; El-Rauof, Fatima A.; Dawoud, H.D. (International Journal of Applied Sciences and Biotechnology, 2015)
Fruit samples of five date cultivars, three cultivars of them were introduced from Emirates Tissue culture Laboratory-Alien Abu Dhabi and cultivated in Haj-Bashir orchard - Khartoum region were collected at the beginning of the Tamar stages. The present study was aimed to investigate the physical and chemical properties. The results showed that the physical characteristics like fruit weight, length, flesh thickness, seed weight differed significantly (P < 0.05) between the various cultivars. Chemical analysis indicated small amounts of crude fiber, crude protein, Fat and ash, while sugars predominated. In general the majority of date cultivars investigated was found to be of the soft date type characterized by the dominance of reducing sugars. The performance of introduced cultivars was well when compared with the indigenous cultivar of most physical, chemical characteristics and general evaluation. Int J Appl Sci Biotechnol, Vol 3(4): 731-736